Analysis of the Influence of Education Level, Wage Level, and Economic Growth on Labor Absorption in Selatan Sulawesi Province - Elpisah, E. (Manunggal Halim Jaya, 2022)
The aims of this research are (1) to analyze and find out whether the variables of education level, wage rate, and economic growth jointly affect the absorption of labor in South Sulawesi Province. The data collection in this study was carried out using the library research method, with observations in 2012 - 2021, the data was obtained from the South Sulawesi Province Bappeda Office, as well as the respective Regency/City Bappeda Offices in Luwu Raya, as well as the Sulawesi Provincial BPS Office. South. Linear Regression Analysis is used to determine the relationship between the independent variable and the dependent variable. The results of the study show that together the independent variables of education level, wage rate, and economic growth have an effect on the dependent variable on employment in South Sulawesi Province during the 2012 - 2021 period. Among the three independent variables, it seems that the wage level is the factor that has the greatest influence on employment absorption in South Sulawesi Province. In connection with the results of this study, it is suggested to the Provincial Government of South Sulawesi to always pay attention to the level of public education, the number of wages received, and efforts to develop various economic sectors in this area so that economic growth can increase which in turn will increase employment and increasing social welfare.